Cálculo do risco de base para Hedgers de venda de soja em Mato Grosso : uma abordagem utilizando cópulas - Marchioro, Luana Witeck (2015)
Brazilian agriculture has stood out on the world stage not only because climatic advantages that provide greater productivity and fertility, but also rely on technological advances that drive changes in the pattern of export of primary products. As soybean production is led by the state of Mato Grosso, we analyzed three places: Sorriso, Campo Novo dos Parecis and Rondonópolis, according to availability of the prices of the physical marked of the Center for Advanced Studies in Applied Economics - ESALQ / USP, in order to make a study for the marketing of this product, through a sale of a hedge. Copulas were calculated to find the joint probabilities, which correspond to the uncertainties of the basic differential, the so-called basis risk. Copulation that best fit the data was Frank, named according to the criterion of maximum likelihood. Finally, were done simulations with price expectations, adopting weakening, strengthening and base of stay for decision making in sales hedgers in Mato Grosso state.